Rare Liraglutide-Induced Dermatological Adverse Reaction in the Treatment of Obesity - Alam, Muhammad Masoud; Rivero-Navea, Giselle; Rivero-Jimenez, Rene Antonio (Journal of Diabetes and Endocrine Practice, 2024)
Liraglutide is a glucagon-like peptide-1 (GLP-1) agonist widely used for managing type 2 diabetes mellitus and obesity. Although allergic reactions to the drug have been documented, skin-related adverse effects remain underreported. We present a case of a 43-year-old woman undergoing subcutaneous liraglutide injections for obesity treatment. Approximately 3 weeks into the treatment regimen, the patient experienced a distinctive reaction characterized by oval, red erythema accompanied by swelling, itchiness, and skin warmth around the injection site shortly after drug administration. This reaction recurred with each subsequent dose over the next 3 days, prompting the patient to discontinue treatment. A dermatology consultant suggested oral antihistamines in conjunction with topical methylprednisolone. Over the course of several days, the intensity of the skin lesions gradually decreased, ultimately resolving completely within 1 month. This case highlights the rarity of skin adverse reactions associated with liraglutide and underscores the importance of recognizing and managing injection site erythema as a potential side effect of this medication. Further research is needed to better understand and document such reactions for improved patient care and safety.
Keywords: diabetes mellitus; drug-induced skin reaction; glucagonlike peptide-1; obesity treatment